2000
DOI: 10.1136/emj.17.2.111
|View full text |Cite
|
Sign up to set email alerts
|

Complications of tube thoracostomy in trauma

Abstract: Objective-To assess the complication rate of tube thoracostomy in trauma. To consider whether this rate is high enough to support a selective reduction in the indications for tube thoracostomy in trauma. Methods-A retrospective case series of all trauma patients who underwent tube thoracostomy during a 12 month period at a large UK teaching hospital with an accident and emergency (A&E) department seeing in excess of 125 000 new patients/ year. These patients were identified using the hospital audit department … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
109
0
7

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(125 citation statements)
references
References 19 publications
9
109
0
7
Order By: Relevance
“…In several studies, the rate of complications was reported to vary between 4.8% and 30% (16)(17)(18)(19)(20), consistent with our study findings (2.2%). Duration of the removal of the tube, length of hospital stay, and development of complications related to the thoracic tube have been associated with severity of injury.…”
Section: Discussionsupporting
confidence: 83%
“…In several studies, the rate of complications was reported to vary between 4.8% and 30% (16)(17)(18)(19)(20), consistent with our study findings (2.2%). Duration of the removal of the tube, length of hospital stay, and development of complications related to the thoracic tube have been associated with severity of injury.…”
Section: Discussionsupporting
confidence: 83%
“…Outcome variables measured included indication for tube placement, chest tube interval (CTI), length of hospital stay (LOHS), mortality, the need for any related intervention (replacement, adjustment of malposition, placement of second chest tube), and the need for surgical intervention (Video-assisted thoracoscopic surgery (VATS), Thoracotomy) and complications. Similarly to the study performed by Bailey, complications were classified as insertional, positional, or infective [3]. Demographic data studied included age, race, gender, injury class and mechanism, prior injuries, Injury…”
Section: Methodsmentioning
confidence: 99%
“…Infections, when they occur, have a tendency to be drain site infections which are minor in nature. Clinically major infections such as an empyema have a relatively low incidence rate [3]. While lateral placement seems to be preferred by most physicians, there is no clinically significant difference between ventral and lateral placement of chest tubes [4].…”
Section: Introductionmentioning
confidence: 99%
“…Chest drain insertions carry a 2%-3% risk [31], but this is increased in the context of trauma [32]. Empirical antibiotics have been shown to be beneficial in reducing the incidence of pleural infection when a chest drain is inserted for trauma [33•, 34]; however, outside this context, there have been no clinical trials evaluating their use and they are not routinely given.…”
Section: Iatrogenic Pleural Infectionmentioning
confidence: 99%